MAKNA SIMBOLIK DALAM TRADISI MELEPASKAN MASA DUKA CITA DI SUKU BABULU,TIMOR LESTE - de Jesus, Domingos Marcal (Linimasa : Jurnal Ilmu Komunikasi, 2025)
ABSTRACT Kore Metan is a tradition in Timor Leste which is still carried out when a family member dies. This research aims to find out the messages contained in the Kore Metan tradition and analyze its symbolic meaning in the Babulu Tribe. The research applies a qualitative descriptive approach using Symbolic Interaction Theory and Cultural Identity Theory. Symbolic Interaction Theory is used to analyze the Self-Concept, Action Concept, Object Concept, Social Interaction Concept, and Collective Action Concept in interactions in the Kore Metan tradition. Primary data was obtained through in-depth interviews and observations, while secondary data was obtained from literature studies. The research results show that the Kore Metan tradition is carried out when a family member dies, with the aim of expressing condolences for one year, since the family member died, using black cloth or Lutu Metan. This tradition has the following symbolic meanings: 1) harmony, togetherness, community self-awareness to carry out traditions from generation to generation, 2) Responsibility in maintaining traditions, 3) Kore Metan is done by removing a black cloth as a symbol of letting go of the period of mourning for the person who died. died, 4) The Kore Metan tradition further strengthens relations between residents through cooperation in organizing events, and 5) There are procedures for implementing the tradition which consists of the planning process, forming a committee, and financial contributions in carrying out the Kore Metan tradition. The core meaning of this tradition is that the people of the Babulu tribe respect their ancestors and carry out this tradition from generation to generation.